PENGARUH METODE SAS BERBANTUAN MEDIA GAMBAR TERHADAP KEMAMPUAN MEMBACA DAN MENULIS PERMULAAN SISWA KELAS I SD NEGERI 1 TAMBLANG - Ni Putu Andini Desiyanti Laksmi; I Nyoman Bawa Bagiada (Nusantara Hasana Journal, 2023)
This study aims to analyze the effect of applying the synthetic structural analytic method (SAS) using image media on the reading and writing abilities of first grade students in elementary school using a quantitative approach. Quasi-experimental research design with a non-equivalent pretest posttest model. The study population was all students of class I SD Negeri 1 Tamblang, North Toraja Regency, totaling 59 students, divided into two study groups with each class IA, namely 29 students, while class IB consisted of 30 students. The sampling technique used the cluster random sampling technique and class IA as the experimental class while class IB as the control class. The data collection technique is using a performance test for writing and a preliminary reading test. based on the comparative analysis of the average reading ability at the beginning of the experimental class and the control class, the value of t = 7.495> 1.69726 and sig. (2-tailed) = 0.001.69726 and sig. (2-tailed) = 0.00 <0.05 this shows that the SAS method has a significant effect on the initial writing ability of class I students of SD Negeri 1 Tamblang